2013
DOI: 10.1590/s1679-45082013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of total hip and knee replacement: a cross-sectional study

Abstract: Objective:To describe the epidemiologic characteristics and adverse events of patients submitted to total hip and total knee replacement.Methods:A cross-sectional study retrospectively assessing medical chart data of all total hip and total knee replacements performed at a private hospital, between January 2007 and December 2010 Patients submitted to total hip and total knee replacement, with consent of surgeons were included. Incomplete records and/or missing data of the hospital database were excluded. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
40
5
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 22 publications
(18 reference statements)
8
40
5
7
Order By: Relevance
“…The results show similar epidemiological characteristics to those of previously published studies; that is, most patients were aged over 65 years, the prevalence of female osteoarthritis was the most common indication for surgery, and SAH was most frequent clinical comorbidity 1, 10, 16, 17, 18…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results show similar epidemiological characteristics to those of previously published studies; that is, most patients were aged over 65 years, the prevalence of female osteoarthritis was the most common indication for surgery, and SAH was most frequent clinical comorbidity 1, 10, 16, 17, 18…”
Section: Discussionsupporting
confidence: 86%
“…Infections are the most feared, prevalent, and studied complications 9 . Diabetes mellitus (DM), hypertension (SAH), and heart diseases are the most prevalent comorbidities among THA patients 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…18,23 Studies show that advanced age is one of the factors for the occurrence of delirium, as well as increased mortality from this cause, 19 which is in agreement with the findings of our study, where the mean age was over 65 years. The increase in age in the general population and the number of diseases related to this increase 14 may lead to an increase in the incidence of delirium, since chronic organic diseases, 13 such as HBP, are risk factors. Metabolic and hydroelectrolytic alterations, although not observed in our study, are reported in the literature as important risk factors for elderly patients suffering from delirium, 24 with the most reported being hypo or hyperglycemia, hypo or hypernatremia, as well as hypo or hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that knee and hip arthroplasty procedures, due to the use of prostheses, and delirium are clinical situations that burden health services, 13 associated with the fact that the restrictions of economic resources lead to a greater emphasis on cost-effectiveness, 25,26 we advocate the need for further studies on the incidence and epidemiology of delirium in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation